Low EVI1 expression at diagnosis identifies a high-risk subgroup in adult Ph-negative B-cell acute lymphoblastic leukemia - Kong, Shu; Wang, Xu; Chen, Wen-Min; Li, Ling-Di; Hao, Yue; Li, Jin-Ying; Xie, Dai-Hong; Li, Zhao-Yu; Lai, Yue-Yun; Jiang, Hao; Jiang, Qian; Qin, Ya-Zhen (Frontiers in Medicine, 2026)
BackgroundThe prognostic impact of EVI1 expression in B-cell acute lymphoblastic leukemia (B-ALL) remains to be explored.MethodBone marrow (BM) samples collected from 436 consecutive newly diagnosed adult Ph-negative B-ALL patients were tested for EVI1 transcript levels using real-time quantitative PCR.ResultThe median EVI1 transcript level in the whole cohort was 0.40% (range: 0.0030–94.3%). Low EVI1 expression defined by lower three quartiles (EVI1 transcript levels was 2.3%) was significantly related to poorer relapse-free survival (RFS) and overall survival (OS) (p = 0.0010 and < 0.0001) and was an independent adverse prognostic factor for RFS (HR (95% confidence interval): 2.3 (1.2–4.1), p = 0.0070) and OS (HR (95% CI): 2.5 (1.3–5.1), p = 0.0090) in the whole cohort. The optimal thresholds for EVI1 transcript levels in the fusion gene subgroups were determined individually, and low EVI1 expression was related to or tended to be related to poorer RFS in patients with TCF3::PBX1, Ph-like fusions, MEF2D fusions, and ZNF384 fusions groups (p = 0.0047, 0.025, 0.032, and 0.070) and was associated with poorer OS in ZNF384 fusions groups (p = 0.012), respectively. Furthermore, patients with TCF3::PBX1 or MEF2D fusion and high EVI1 expression had RFS and OS similar to those without the corresponding fusions, and patients with ZNF384 fusion and low EVI1 expression had RFS and OS comparable to those without ZNF384 fusions (all p > 0.05).ConclusionLow EVI1 transcript levels at diagnosis are related to poor prognosis in adult Ph-negative B-ALL, and EVI1 expression may improve fusion gene-defined risk stratification.